Corporate image and corporate identity strategy in Malaysia - Teo, Meng Meng (1997)
The main aim of this study is to study the Corporate Image and Corporate Identity Strategy in Malaysia. A survey was conducted amongst personal investors, corporate executives, directors, senior managers, bankers and institutional professionals from various companies. The data was collected by personal interviews with thirty respondents. The findings indicated that corporate image and corporate identity both are vital for success of a company. The test results also shown that visual identity was directly influenced by public perception, it was a dependent variable to the visual identity. Furthermore, the visual identity was indirectly influenced by the media, which means that the media was an independent variable. Lastly, the findings shown that the effectiveness of a Corporate Image and Corporate Identity can help to increase awareness of the company in line with the company's objectives, for instance, to raise the stock price in the share market, to boot up the sales, and to encourage more investment. Based on this finding, a model as described in Graph 2 is proposed to hypothesise the relationship between Corporate Image and Corporate Identity. In this study, some implications and some prescriptive recommendations are made about how the companies can enhance their projected image and the corporate identity.